External Morphology of the Larvae of Clostera Fulgurita Wlk. and Clostera Restitura Wlk. (Lepidoptera: Notodontidae) - Joshi, K. C.; Gurung, D.; Sarma, P. C. (Indian Forester, 1989)
The poplars are defoliated by two species of poplar defoliators viz. Clostera fulgurita and C. restitura in N.E. region of India In the present article, the morphological characters and the chaetotaxy of their larvae have been described and compared. A key to identify both the species is also given.